2019
DOI: 10.1016/j.tem.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Progenitors: There and Back Again

Abstract: Adult pancreatic regeneration is one of the most contentious topics in modern biology. The decades-long view that the islets of Langerhans can be replenished throughout adult life through the reactivation of ductal progenitor cells has been replaced over the last decade by the now prevailing notion that regeneration does not involve progenitors and occurs only through the duplication of pre-existing mature cells. Here we dissect the limitations of lineage tracing to draw categorical conclusions about pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…The case for neogenesis, especially in basal conditions, has been much more controversial, with almost an equal number of studies providing evidence to support the neogenesis hypothesis as there are refuting it (reviewed in [ 38 ]). One major hindrance to these studies has been the failure to identify a stem cell marker that would allow for lineage tracing to clearly identify newly formed beta cells.…”
Section: Intrinsic Beta Cell Mass Expansionmentioning
confidence: 99%
“…The case for neogenesis, especially in basal conditions, has been much more controversial, with almost an equal number of studies providing evidence to support the neogenesis hypothesis as there are refuting it (reviewed in [ 38 ]). One major hindrance to these studies has been the failure to identify a stem cell marker that would allow for lineage tracing to clearly identify newly formed beta cells.…”
Section: Intrinsic Beta Cell Mass Expansionmentioning
confidence: 99%
“…In recent years, the transdifferentiation of pancreatic endocrine cells into beta cells was proved to be a promising method [34]. After a decade of relative discredit, the progenitor cell hypothesis made a figurative journey back into favor [35]. In our study, we assessed the three origins of newborn beta cells, including beta cell self-replication, alpha to beta cell transdifferentiation and duct-derived beta cell neogenesis, and found that all the three paths contributed to the dapagliflozininduced beta cell regeneration.…”
Section: Protective Effects Of Sglt2 Inhibitors On Pancreatic Beta Cellsmentioning
confidence: 99%
“…Additionally, non-β endocrine cells, pancreatic exocrine cells, and even nonpancreatic cells such as intestinal enteroendocrine cells have been demonstrated to transdifferentiate into insulin-secreting cells by reprogramming in some cases (Thorel et al, 2010 ; Chen et al, 2014 ; Lemper et al, 2015 ). However, genetic lineage-tracing studies indicated that the exocrine compartment was unlikely to contribute to the formation of endocrine cells in vivo (Aguayo-Mazzucato and Bonner-Weir, 2018 ; Dominguez-Bendala et al, 2019 ). The current dominant view is that the replenishment of adult pancreatic β cells relies principally on their self-duplication instead of potential pancreatic stem cell differentiation (Dor et al, 2004 ).…”
Section: State-of-the-art Strategies To Establish Islet Organoidsmentioning
confidence: 99%